2023
DOI: 10.3390/ijms24032942
|View full text |Cite
|
Sign up to set email alerts
|

The Intracellular and Secreted Sides of Osteopontin and Their Putative Physiopathological Roles

Abstract: Classically, osteopontin (OPN) has been described as a secreted glycophosprotein. Indeed, most data concerning its physiological and pathological roles are mainly related to the secreted OPN (sOPN). However, there are several instances in which intracellular OPN (iOPN) has been described, presenting some specific roles in distinct experimental models, such as in the immune system, cancer cells, and neurological disorders. We herein aimed to highlight and discuss some of these secreted and intracellular roles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 87 publications
0
24
0
Order By: Relevance
“…sOPN exerts its effect via binding to integrin receptors, the hyaluronan receptor CD44, and the epidermal growth factor receptor (EGFR), and thus functions as a cytokine. For a detailed overview of the reported functions of sOPN, we refer to the review of Bastos et al [41 ▪▪ ]. OPN can also be retained intracellularly as a result of alternative translation (iOPN, intracellular OPN) [42].…”
Section: The Pleiotrope Role Of Osteopontinmentioning
confidence: 99%
“…sOPN exerts its effect via binding to integrin receptors, the hyaluronan receptor CD44, and the epidermal growth factor receptor (EGFR), and thus functions as a cytokine. For a detailed overview of the reported functions of sOPN, we refer to the review of Bastos et al [41 ▪▪ ]. OPN can also be retained intracellularly as a result of alternative translation (iOPN, intracellular OPN) [42].…”
Section: The Pleiotrope Role Of Osteopontinmentioning
confidence: 99%
“…It has been demonstrated that OPN has a role in promoting tumor growth and facilitating metastasis formation by promoting angiogenesis and modulating the immune response 7,8 . OPN is encoded by the SPP1 gene that is localized on chromosome 4q22.1, and consists of seven exons, from which exon 1 is untranslated, and exons 2–7 contain the coding sequences 3 . OPN protein has two terminal zones including C‐terminal, which binds heparin molecules, such as CD44, and N‐terminal, which binds integrin receptors 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Osteopontin (OPN) plays an important role in regulating various physiological processes, including bone metabolism, immune response, wound healing, cell adhesion, cell migration, and inflammation 1–3 . Many studies have described that OPN is involved in the pathogenesis of various diseases, including different types of cancer, cardiovascular diseases, and autoimmune disorders 4–6 .…”
Section: Introductionmentioning
confidence: 99%
“…IAV infections trigger host antiviral mechanisms that modulate human signaling cascades that modify pro-inflammatory cytokines, including osteopontin (OPN). This protein is a member of the group of small integrin-binding ligand N-linked glycoproteins (SIBLING) and participates in distinct physiological and pathological conditions such as bone remodeling, inflammation, and oncogenesis [ 18 , 19 ]. OPN is produced by different cell types, including endothelial, epithelial, and immune cells, activating them in response to stimuli such as viral infections [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…This protein is a member of the group of small integrin-binding ligand N-linked glycoproteins (SIBLING) and participates in distinct physiological and pathological conditions such as bone remodeling, inflammation, and oncogenesis [ 18 , 19 ]. OPN is produced by different cell types, including endothelial, epithelial, and immune cells, activating them in response to stimuli such as viral infections [ 19 , 20 , 21 ]. Previous reports demonstrated that OPN transcript levels were higher in the blood samples of IAV patients than in healthy controls [ 22 ].…”
Section: Introductionmentioning
confidence: 99%